Recent trends and advances in the epidemiology, synergism, and delivery system of lycopene as an anti-cancer agent. (August 2021) - Song, Xunyu; Luo, Yinghua; Ma, Lingjun; Hu, Xiaosong; Simal-Gandara, Jesus; Wang, Li-Shu; Bajpai, Vivek K.; Xiao, Jianbo; Chen, Fang
Abstract: Dietary interventions are key nutritional strategies to prevent, improve, and prolong the survival of cancer patients. Lycopene, one of the strongest natural antioxidants, and its biologically active metabolites, have shown significant potential to prevent a variety of cancers, including prostate, breast, and stomach cancers, making it a promising anti-cancer agent. We review the potential regulatory mechanisms and epidemiological evidences of lycopene and its metabolites to delay the progression of cancers at different developmental stages. Recent studies have revealed that lycopene and its metabolites mediate multiple molecular mechanisms in cancer treatment such as redox homeostasis, selective anti-proliferation, apoptosis, anti-angiogenesis, tumour microenvironment regulation, and anti-metastasis and anti-invasion. Gut microbes and cholesterol metabolism are also the potential regulation targets of lycopene and its metabolites. As a dietary supplement, the synergistic interaction of lycopene with other drugs and nutrients is highlighted especially due to its binding activity with other nutrients in the diet found central to the fight against cancer. Furthermore, the application of several of novel lycopene delivery carriers are on the rise including nanoemulsions, nanostructured liposomes, and polymer nanoparticles for cancer prevention as discussed in this review with future needed development. Moreover, the synergistic mechanism between lycopene and other nutrients or drugs and novel delivery systems of lycopene should now be deeply investigated to improve its clinical application in cancer intervention in the future.